2017
DOI: 10.1111/acer.13490
|View full text |Cite
|
Sign up to set email alerts
|

The Spirit Is Willing, But the Flesh is Weak: Why Young People Drink More Than Intended on Weekend Nights—An Event‐Level Study

Abstract: Making young adults aware of the tendency to drink more than intended, particularly when drinking begins early in the evening, moves from location to location, and includes large groups of friends, may be a fruitful prevention target. Structural measures, including responsible beverage service, may also help in preventing excessive drinking at multiple locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…In fact, results showed that annotators' and the algorithms' ratings explained more variance in private places and in commercial venues, but that participants' ratings explained more variance in outdoor locations. In the present case, in line with the finding that contextual characteristics were weakly associated with alcohol use in public spaces, these results suggest that the choice of drinking alcohol in such locations might rather relate to other factors (e.g., night-level drinking intentions [61], off-licensed alcohol prices [62]) that could be better reported subjectively by the participants than sensed by observers.…”
Section: Plos Onesupporting
confidence: 88%
“…In fact, results showed that annotators' and the algorithms' ratings explained more variance in private places and in commercial venues, but that participants' ratings explained more variance in outdoor locations. In the present case, in line with the finding that contextual characteristics were weakly associated with alcohol use in public spaces, these results suggest that the choice of drinking alcohol in such locations might rather relate to other factors (e.g., night-level drinking intentions [61], off-licensed alcohol prices [62]) that could be better reported subjectively by the participants than sensed by observers.…”
Section: Plos Onesupporting
confidence: 88%
“…As central mechanisms of action, the TIPs are designed to increase self-monitoring and promote awareness of potential discrepancies between drinking intentions and actual consumption, thereby raising the awareness of ambivalence as an important mechanism in the development of a motivation to change according to MI theory [44]. According to a recent study, 40% of adolescents and young adults (aged 16–25 years) consume alcohol heavily despite they intent not to [48]. Individualised feedback on this discrepancy embedded in real-life context was found to be effective in reducing heavy drinking [33].…”
Section: Methodsmentioning
confidence: 99%
“…On Saturdays and Sundays, the application prompted participants to indicate the total number of alcoholic drinks they had consumed the previous night using a slider ranging from 0 to 30 drinks. The questionnaire could be completed between 10 a.m. and 4 p.m. Each drink corresponded to approximately 10 g of pure ethanol .…”
Section: Methodsmentioning
confidence: 99%